Challenging the human trafficking narrative: victims, villains, and heroes - O'Brien, Erin E. (Victims, culture and society, 2019)
Cover; Title; Copyright; Dedication; Contents; Acknowledgements; 1 Introduction: the narrative code; 2 Telling trafficking stories; 3 From sex slaves to migrant men; 4 Ideal and invisible victims; 5 Pimps, johns and mobsters; 6 Heroic consumers; 7 Everyday activists and action heroes; 8 Government heroes and villains; 9 Conclusion: narrative evolution; Index